Enhancement of quantum synchronization in optomechanical system by modulating the couplings. (26th February 2018) - Geng, H; Du, L; Liu, H D; Yi, X X
Abstract: We study two coupled optomechanical systems interact mutually through an optical fiber and a phonon tunneling, which are controlled by two switches K 1 and K 2 . Compared to the quantum synchronization of the optomechanical systems without modification, we find that a proper periodic modification by different switches setups can achieve a better quantum synchronization. In addition, we also analyze the robustness of the periodically modified system against the bath's mean temperature or the oscillators' frequency difference, respectively.